PTEN Expression, Not Mutation Status in TSC1, TSC2 , or mTOR , Correlates with the Outcome on Everolimus in Patients with Renal Cell Carcinoma Treated on the Randomized RECORD-3 Trial - Voss, Martin H.; Chen, David; Reising, Albert; Marker, Mahtab; Shi, Jiayuan; Xu, Jianning; Ostrovnaya, Irina; Seshan, Venkatraman E.; Redzematovic, Almedina; Chen, Ying-Bei; Patel, Parul; Han, Xia; et al. (Clinical cancer research, 2019)
Genomic alterations in key components of PI3K/mTOR pathway have been proposed as candidate predictive markers for rapalog therapy in renal cell carcinoma (RCC). We tested this hypothesis in patients from a randomized phase II trial of everolimus versus sunitinib. Archival specimens collected at baseline were analyzed with targeted next-generation sequencing (NGS). Focus of interest were alterations in key PI3K pathway components. PTEN expression was assessed by IHC. Association between molecular findings and treatment outcomes was investigated; same associations were tested for 2 everolimus-treated trial cohorts in gastric and hepatocellular carcinoma (HCC). Among 184 everolimus-treated patients with RCC with NGS data, mutation rates in genes of interest were 6% ( ), 4.4% ( ), and 8.2% ( ); 44% harbored alterations in ≥1 PI3K pathway component. For subjects with presence versus absence of mutations in , or progression-free survival (PFS) neither differed on univariate analysis (HR, 1.0; = 0.895) nor on multivariate testing stratified by MSKCC risk group and other established prognostic factors (HR, 1.1; = 0.806). Everolimus-treated patients with retained ( = 50) versus lost ( = 50) PTEN IHC expression had median PFS of 5.3 months versus 10.5 months (HR, 2.5; < 0.001). Such differences were not seen with sunitinib (10.9 months vs. 10.3 months; HR, 0.8; = 0.475). Molecular findings did not correlate with outcomes in gastric and HCC cohorts. Association between mutation status for / / and therapeutic outcome on everolimus was not confirmed. Clinically meaningful differences in PFS were seen based on PTEN expression by IHC, lost in >50% of patients.